2017
DOI: 10.3390/rs9111099
|View full text |Cite
|
Sign up to set email alerts
|

Linear Multi-Task Learning for Predicting Soil Properties Using Field Spectroscopy

Abstract: Abstract:Field spectroscopy has been suggested to be an efficient method for predicting soil properties using quantitative mathematical models in a rapid and non-destructive manner. Traditional multivariate regression algorithms usually regard the modeling of each soil property as a single task, which means only one response variable is considered as the output during modeling. Therefore, these algorithms are less suitable for the prediction of several key soil properties with low concentrations or unobvious s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…Because the field spectral reflectance is sensitive to interference with the atmospheric water absorption [34], reflectance spectra of these 91 fresh soil samples were acquired in the laboratory. An ASD FieldSpec 3 spectrometer with a spectral range of 350-2500 nm was applied to measure the soil VIS-NIR spectra.…”
Section: Spectral Measurement and Pre-processingmentioning
confidence: 99%
“…Because the field spectral reflectance is sensitive to interference with the atmospheric water absorption [34], reflectance spectra of these 91 fresh soil samples were acquired in the laboratory. An ASD FieldSpec 3 spectrometer with a spectral range of 350-2500 nm was applied to measure the soil VIS-NIR spectra.…”
Section: Spectral Measurement and Pre-processingmentioning
confidence: 99%
“…Qi et al [16] collected and analyzed soil spectra and soil samples from four watersheds in Israel and compared the relative performances of the linear multi-task learning (LMTL) algorithm and the partial least squares regression (PLS-R) single-task learning algorithm to derive different soil properties. The authors found that the multi-task algorithm had a slightly higher retrieval capability and was able to assess the organic matter with a good accuracy and a ratio of performance to deviation (RPD) higher than 2, the Ph, amount of nitrogen, phosphorus, and water content with a moderate accuracy (RPD between 1.4 and 2), and the amount of potassium and the electrical conductivity with a lower accuracy (RPD lower than 1.4).…”
Section: Soil Spectroscopymentioning
confidence: 99%
“…Using field and laboratory-based spectroscopy, Liu et al [15] and Qi et al [16] demonstrated the potential of airborne and satellite hyperspectral measurements for large-scale soil property monitoring and mapping.…”
Section: Soil Spectroscopymentioning
confidence: 99%
“…The explanatory power of the independent variables to the dependent variables is achieved by calculating the VIP score. The independent variables are sequenced according to the explanatory power (Qi et al 2017). The VIP score for the j-th variable is given as:…”
Section: Variable Importance In Projection (Vip)mentioning
confidence: 99%
“…Plenty of studies have demonstrated that spectral variable selection methods can not only reduce the complexity of calibration models, but also improve the model predictive performance (Hong et al 2018a). To select the optimal spectral variable subset, scholars have investigated varied methods such as gray correlation (GC) (Li et al 2016;Wang et al 2018b), stepwise regression (SR) (Zhang et al 2018) and variable importance in projection (VIP) (Qi et al 2017), and have achieved satisfactory effects. In addition, all the three methods have been widely applied in many studies, such as plant physiology, food engineering, mathematical statistics (Oussama et al, 2012;Maimaitiyiming et al 2017;Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%